2017
DOI: 10.1056/nejmoa1607033
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo-Controlled Trial of Antibiotics for Smaller Skin Abscesses

Abstract: As compared with incision and drainage alone, clindamycin or TMP-SMX in conjunction with incision and drainage improves short-term outcomes in patients who have a simple abscess. This benefit must be weighed against the known side-effect profile of these antimicrobials. (Funded by the National Institutes of Health; ClinicalTrials.gov number, NCT00730028 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
120
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(130 citation statements)
references
References 17 publications
3
120
0
7
Order By: Relevance
“…There have been few prospective randomized trials exploring variations in the treatment of skin abscesses outside of antibiotics. The 2 most recent large randomized controlled trials on antibiotics and abscess drainage demonstrated a benefit from antibiotics, 11,12 but neither study included the use of ultrasonography as a possible confounder for its results. In the current study, antibiotic use was not associated with clinical cure.…”
Section: Discussionmentioning
confidence: 99%
“…There have been few prospective randomized trials exploring variations in the treatment of skin abscesses outside of antibiotics. The 2 most recent large randomized controlled trials on antibiotics and abscess drainage demonstrated a benefit from antibiotics, 11,12 but neither study included the use of ultrasonography as a possible confounder for its results. In the current study, antibiotic use was not associated with clinical cure.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the size of the abscess, incision and drainage may also be sufficient for infections with community‐acquired (CA) MRSA . […] Given the high prevalence of PVL‐positive MRSA (USA300), the results from recent studies on abscesses and ABSSSI conducted in the US cannot be directly compared to the situation in Central Europe […].…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of trimethoprim/sulfamethoxazole resistance in an emerging sequence type 5 methicillin-resistant Staphylococcus aureus clone reveals discrepant resistance reporting In regions where community-acquired methicillin-resistant Staphylococcus aureus (MRSA) is common, oral trimethoprim/sulfamethoxazole (SXT) is a treatment option for skin and soft tissue infections. Recent trials have demonstrated noninferiority of SXT compared to intramuscular benzathine benzylpenicillin [1] or oral clindamycin [2] for treatment of uncomplicated skin and soft tissue infections such as impetigo [1], cellulitis and simple abscesses [2]. Concern over the increasing rates of community-acquired S. aureus isolates reported as SXT resistant has resulted in recommendations against prescribing SXT for the treatment of skin and soft tissue infections in the Kimberley region of Western Australia [3].…”
mentioning
confidence: 99%